O discurso sobre a felicidade como prática de biopolítica em capas e matérias de revistas digitais e impressas - Peixoto, Kamila Nogueira (2018)
Throughout the history of thought, there was struggle and dispute about he conditions for having a happylife. However, not all of the periods have put the happiness as a goal to be achieved (KARNAL, 2016, p. 9). Nowadays, the continuous ly search for a happy way of life has become na obligation. In view of the above, the general purpose of this work is to analyse the discourse of happiness used as biopolitical strategy in covers of printed and digital magazines. We will use the theoretical and methodology ical premise from Discourse Analysis, with quotes from Michel Foulcault about genealogy of power, bringing the possibility of analyzing there lations between the discourses, the subjects, history and powers in society. In a methodological way, this research is qualitative, descriptive and explanatory. For the analysis of the corpus, we will use Foucault'sarche genealogical method, which allowsus to use history to explain, here, how the media is imposing happiness, the interdiction of sadness and the transformations in the promotion of new forms of subjectivity anchored in regimes of truth, which under pinand stimulate the incessant search for happiness today. The corpus is made of seven magazine covers with editions from 2012 to 2018 (digital and printed) and its subjects, always with the theme of happiness. As results, we can say that he need, of social support, acquires two aspects: the economic one, because the subject has a series of conditions to be fulfilled to achieve a happiness always partial and relative that justifies the continuous search and turns the capital; and the psychological, which expresses the, desires and needs of the subject, that is to say, everything that is missing, which escapes him, but is passed through the media with something palpable, satisfactory, achievable and permanent; a choice of each. Thus, through biopolitical strategies, the media imposes subtly, in the form of desire, causing the subject to see incessantly what is outside, wishing a distant reality.